2017
DOI: 10.3389/fnagi.2017.00119
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Prefrontal Short—Latency Afferent Inhibition in Older Adults and Its Relation to Executive Function: A TMS-EEG Study

Abstract: Combining transcranial magnetic stimulation (TMS) with electroencephalography (EEG) allows for the assessment of various neurophysiological processes in the human cortex. One of these paradigms, short-latency afferent inhibition (SAI), is thought to be a sensitive measure of cholinergic activity. In a previous study, we demonstrated the temporal pattern of this paradigm from both the motor (M1) and dorsolateral prefrontal cortex (DLPFC) using simultaneous TMS–EEG recording. The SAI paradigm led to marked modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…Studies have reported N100 to be associated with GABA B -mediated inhibitory mechanisms in both motor (Bonnard et al, 2009;Farzan et al, 2013;Premoli, Rivolta, et al, 2014b;Rogasch, Daskalakis, et al, 2013a) and prefrontal cortex (Chung et al, 2017;Rogasch et al, 2015). The amplitude of N100 increased following SAI both in motor and prefrontal cortex (Noda et al, 2016;Noda, Zomorrodi, Backhouse, et al, 2017c), but decreased following cerebellar iTBS (Casula, Pellicciari, Ponzo, et al, 2016b), which are in line with the change observed in N100 following Ind iTBS. However, our previous studies showed increased N100 following prefrontal iTBS (50 Hz at 5 Hz) (Chung et al, 2017;Chung, Rogasch, Hoy, & Fitzgerald, 2018a;Chung, Rogasch, Hoy, Sullivan, et al, 2018b), and the discrepancy of the outcome…”
Section: Effect Of Individualised Itbs On Plastic Effects In the Prsupporting
confidence: 72%
See 2 more Smart Citations
“…Studies have reported N100 to be associated with GABA B -mediated inhibitory mechanisms in both motor (Bonnard et al, 2009;Farzan et al, 2013;Premoli, Rivolta, et al, 2014b;Rogasch, Daskalakis, et al, 2013a) and prefrontal cortex (Chung et al, 2017;Rogasch et al, 2015). The amplitude of N100 increased following SAI both in motor and prefrontal cortex (Noda et al, 2016;Noda, Zomorrodi, Backhouse, et al, 2017c), but decreased following cerebellar iTBS (Casula, Pellicciari, Ponzo, et al, 2016b), which are in line with the change observed in N100 following Ind iTBS. However, our previous studies showed increased N100 following prefrontal iTBS (50 Hz at 5 Hz) (Chung et al, 2017;Chung, Rogasch, Hoy, & Fitzgerald, 2018a;Chung, Rogasch, Hoy, Sullivan, et al, 2018b), and the discrepancy of the outcome…”
Section: Effect Of Individualised Itbs On Plastic Effects In the Prsupporting
confidence: 72%
“…A growing body of evidence suggests P60 may provide a marker of cortical excitability. In the prefrontal cortex, SAI resulted in a reduction of this component (Noda, Zomorrodi, Backhouse, et al, 2017c). a Not adding up to 100% due to 1 subject having no differences in score change (Δ = 0).…”
Section: Effect Of Individualised Itbs On Plastic Effects In the Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in working memory and other cognitive functions supported by the dlPFC are widely reported in older adults (Alexander et al, 2012; Daigneault and Braun, 1993; Langley and Madden, 2000; MacPherson et al, 2002; Noda et al, 2017). In stark contrast to the associations between working memory impairment and intertemporal choice described above, however, advanced age is accompanied by an increased ability to forgo immediate gratification in favor of delayed rewards (Green et al, 1999, 1996; Jimura et al, 2013; Samanez-Larkin et al, 2011; Simon et al, 2010).…”
Section: 0 Introductionmentioning
confidence: 99%
“…In the reviewed studies, only two explored the relation between cognition and TMS‐EEG, linking deficits in working memory and executive functions with GABAergic and cholinergic impairments, respectively. This relationship is also poorly explored in healthy controls, with only a handful of studies linking TMS‐EEG measures in the DLPFC with cognitive functions, such as LICI and working memory, and SAI and executive functions . TMS‐EEG can be a powerful method allowing measurement of the involvement of several neurotransmitter systems in specific cognitive domains in psychiatry, and future studies should definitively explore this extensively.…”
Section: Toward a Shared Biomarker Of Mental Health Disordersmentioning
confidence: 99%